Labor Markets as Human Ecosystems: The Insider-Outsider Theory Reconsidered - Dennis J. Snower (Institute of Labor Economics (IZA), 2025)
Whereas labor markets are traditionally viewed as machine-like environments – where agents, coordinated by price signals, solve constrained optimization problems or adhere to established heuristics – this paper views labor markets as human ecosystems, containing living things, namely, the human beings who participate in these markets. Living things adapt to their environment and evolve across their domains of life. Consequently, activities in labor markets cannot be understood independently of their social and political foundations. Labor markets are embedded in social, economic, political and environmental systems, and their adaptiveness to their social and natural environments. In this context, the insider-outsider theory may be generalized by reconceptualizing insiders and outsiders in terms of their relative adaptive advantages and the structural barriers to adaptation. The functions and misfunctions of adaptively embedded labor markets can be specified in terms of the adaptiveness as systems or the adaptiveness of the components of these systems. The ecosystemic approach also involves a reconceptualization of agents operating in labor markets, implying a new theories of the firm and workers.
Keywords: J0; J2; J6; 330; insider-outsider theory; embedded labor markets; evolution; theory of the firm